Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/jcp.21732
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic stem cell technologies and drug discovery

Abstract: Development of new drugs is costly and takes huge resources into consideration. The big pharmaceutical companies are currently facing increasing developmental costs and a lower success-rate of bringing new compounds to the market. Therefore, it is now of outmost importance that the drug-hunting companies minimize late attritions due to sub-optimal pharmacokinetic properties or unexpected toxicity when entering the clinical programs. To achieve this, a strong need to test new candidate drugs in assays of high h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 49 publications
0
69
0
Order By: Relevance
“…This may be of particular value for new emerging technology such as stem cell manufacturing, where the cellular transformation process is quite different from traditional bioprocesses, and where scale-up principles are at present not founded [6,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be of particular value for new emerging technology such as stem cell manufacturing, where the cellular transformation process is quite different from traditional bioprocesses, and where scale-up principles are at present not founded [6,39].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing industrial use of mammalian cell cultures for a variety of purposes, such as production of biopharmaceuticals [3][4][5] and expansion and differentiation of embryonic stems [6][7][8][9], emphasizes the need of reliable and successful scale-up methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they have been considered as a source of various cell types for organ regeneration or tissue replacement after injury or disease (Odorico et al 2001). It has also been postulated that hES cells could be used for reproductive toxicity screening in vitro (Krtolica & Giritharan 2010) as well as for drug discovery to minimize unexpected toxicity when entering a clinical trial (Jensen et al 2009). Using undifferentiated hES cells in an in vitro screening assay, Kim et al (2006) reported that exposure to the organic compounds such as nonylphenol (NP) and octylphenol (OP) decreased expression of Oct4 and Nanog in a dose-dependent manner.…”
Section: Susceptibility Of Embryonic Stem Cells To Edc Exposurementioning
confidence: 99%
“…Thus, many scientists working on optimization of functions of hepatic cell cultures, and applicability of such cells in safety studies, are exploring the use of three-dimensional (3D) cell systems. This includes seeding matrix-like scaffolds in multiwell formats or using more advanced and organ-like setups like various bioreactors [28]. Moreover, the use of different liver cell types such as endothelial cells, Kuppfer cells, or Stellate cells in combination with hepatocytes in these models may increase assay predictability.…”
Section: Hpsc-derived Hepatocytes In Toxicity Testingmentioning
confidence: 99%